PENGARUH KARAKTERISTIK INDIVIDU DAN KARAKTERISTIK PEKERJAAN TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) MELALUI KEPUASAN KERJA PEGAWAI PADA KANTOR DINAS KESEHATAN KOTA TABANAN - I Kadek Widiantara; Made Juliasa; Ni Luh Indiani (Yayasan Nusantara Hasana Berdikari, 2026)
This study aims to determine the effect between individual characteristics (X1) and job characteristics (X2) on organizational citizenship behavior (Y) through job satisfaction (Z) of employees at the Tabanan City Health Office. This type of research uses causal associative research. The data collection method used is the census method which is carried out on 79 employees of the Tabanan City Health Office. The type of data used in this study uses quantitative data. The data analysis technique in this study used structural equation modeling partial least square (SEM-PLS) version 4.1.1. The results obtained in this study are: (1) individual characteristics have a positive and significant effect on organizational citizenship behavior, (2) job characteristics have a positive and insignificant effect on organizational citizenship behavior, (3) individual characteristics have a positive and significant effect on job satisfaction, (4) that job characteristics have a positive and significant effect on job satisfaction, (5) job satisfaction has a positive and significant effect on organizational citizenship behavior, (6) individual characteristics have a positive and significant effect on organizational citizenship behavior through job satisfaction, (7) job characteristics have a positive and significant effect on organizational citizenship behavior through job satisfaction.